1H1 NMR and XRD Spectra of the Reaction Product of Hexahydro Cyclotriphosphazene with Cu(II) - SINGH, YOGENDRA PAL; JADON, S.P.S. (Asian Journal of Chemistry, 2010)
1H1 NMR and X-ray diffraction spectra of the reaction products of hexahydrocyclophosphazene with Cu(II) acetate, synthesized and termed as Cu(II)A and Cu(II)B, recorded, explain their distorted hexagonal and triclinic structure, respectively.